A Digitalization in Banking Industry: Impact of Interface Design on Customer Loyalty of Mobile Banking in Indonesia - Anita, Dwi Anita (International Journal of Business Studies, 2024)
This research is a study to analyze the effect of Interface Design on customer loyalty in mobile banking applications in Indonesia. This research methodology uses a questionnaire distribution technique for millennial generation respondents who use mobile banking in Indonesia, using the Likert Scale method, and data processing techniques using the Structural Equation Modeling (SEM) method. This research aims to examine the significant influence of Interface Design on customer loyalty in mobile banking applications in Indonesia. This digital transformation in the banking industry provides benefits for both banks and their customers. Banking digitalization can provide benefits for accelerating customer transactions, avoiding human errors for manual transactions at offline branches, and increasing banks’ efficiency because it reduces manual processes in serving customer transactions. For customers, mobile banking applications accelerate transactions, time efficiency without having to come to an offline branch, and flexibility to create transactions. The hypothesis indicates that interface design significantly impacts loyalty customers using mobile banking applications. This research is useful for the banking industry to accommodate a user-friendly interface design to increase the competitive advantage for banks that provide mobile banking applications.